Structural and functional basis of the developmental regulation of human coagulation factor IX gene: factor IX Leyden. - Hirosawa, S (1990)
Hemophilia B Leyden is characterized by unusual developmental regulation of factor IX synthesis in affected individuals. One family affected with the hemophilia B Leyden phenotype was found to have a specific single-base mutation (G----A) at nucleotide -6 of the factor IX gene. The mutation site was found in a small region of the 5'-untranslated sequence designated the Leyden-specific region (LS region). This region, approximately 40 base pairs in length, contains the unique mutation sites of all the known factor IX Leyden genes (five families) analyzed to date. This fact strongly suggests that the LS region is directly or indirectly involved in the developmental regulation of factor IX biosynthesis. Base changes at nucleotide -20 as well as at nucleotide -6 and deletions of the 3' half of the LS region reduced expression activity of the factor IX gene to approximately 15-31% that of the normal control, as assessed in a cultured cell (HepG2) expression system. The LS region binds at least two proteins. Androgen significantly increased the transcriptional activities of both mutant and normal factor IX genes in a concentration-dependent manner.